Cucumber Mosaic Virus: Global genome comparison and beyond - LEONARD, WHYE KIT LIM; Hung, Ing Mee; Chung, Hung Hui (Malaysian Society of Microbiology, 2022)
Aims: The cucumber mosaic virus (CMV) is categorized under the genus Cucumovirus and family Bromoviridae. This virus is known to infect over 1200 plant species from 100 families, including ornamental and horticultural plants. In this study, we pioneered a global genome comparison to decipher the unknown orchestrators behind the virulence and pathogenicity of CMV via the discovery of important single nucleotide polymorphic markers. Methodology and results: As a result, the genome size was found to be a potential preliminary country-specific marker for South Korea and the GC content can be utilized to preliminarily differentiate Turkey isolates from the others. The motif analysis as well as whole genome and coat protein phylogenetic trees were unable to form country-specific clusters. However, the coat protein haplotype analysis had successfully unconcealed country-specific single nucleotide polymorphic markers for Iran, Turkey and Japan isolates. Moreover, coat protein modelling and gene ontology prediction depicted high conservation across CMV isolates from different countries. Conclusion, significance and impact of study: The country-specific single nucleotide polymorphic markers unearthed in this study may provide significant data towards the profiling of varying virulence and pathogenicity of CMV across the globe in time to combat the yield loss driven by this virus thru the most efficacious biological control measures in the future.